Impact of Working Capital and Leverage on Profitability: A Comparison between Indonesia Ulama Council Fatwa and AAOIFI Sharia Standards - Akhmad - Sultoni; Rahmat Mulyana; Saiful Anwar (The Accounting Journal of Binaniaga, 2021)
Purpose – This study aims to provide empirical evidence regarding the restrictions on the sharia stock criteria, by observing the impact of working capital and leverage on the profitability of companies listed in Indonesia Sharia Stock Index. There are some differences between Indonesia Ulama Council’s fatwa and AAOIFI sharia standards regarding the restrictions on the sharia stocks, particularly on the riba based leverage compared to the total assets of the companies regarded as having sharia stocks. The objective of this paper is to compare and analyze which restrictions serves companies better.Design/methodology/approach – The research was done to companies listed in Indonesia Sharia Stock Index from 2012 until 2018. Panel data regression was applied to analyze the significance of the result. For comparison purpose of the fatwa and the AAOIFI sharia standards, samples were divided into three different groups based on the debt to assets ratio as an indicator of the riba based leverage (≤30%, 30%-45% and>45%). Variables of cash conversion cycle and debt to assets ratio are used to measure the impact of the working capital and leverage on the return on assets as indicator or profitability.Findings – The result suggests that there are differences in the impact of working capital and leverage on the profitability for the three groups of leverage. In favor of the AAOIFI sharia standards, the result of this study shows that in the group where the leverage is 30% at maximum, the profitability is not affected by the working capital and leverage of the company. Meanwhile, in the group where the leverage is more than 30%, the impact of working capital and leverage on the profitability of the company is found to be significant.Research limitations/implications – This study is limited to the companies listed in Indonesia Sharia Stock Index, with variables of cash conversion, debt to assets ratio and return on assets.Practical implications – This study provide an empirical evidence that can be used to revisit the restrictions applied by Indonesia Ulama Council regarding the sharia stocks.Originality/value – To the best of authors’ knowledge, this paper provides important findings in the sharia finance dynamic in Indonesia.Keyword working capital, leverage, profitability, sharia stocks.Paper type research paper